Imaginary neighbors : mediating Polish-Jewish relations after the Holocaust - Glowacka, Dorota, 1960-; Zylinska, Joanna, 1971- (University of Nebraska Press, 2007)
Imaginary Neighbors offers a unique and significant contribution to the contemporary debate concerning Holocaust memory by exploring the most important current political topic in Poland: Jewish-Polish relations during and after World War II.